Promoting Secure Attachment in Children without Parental Care in Egypt - Nada, Manar (AUC Knowledge Fountain, 2022)
In Egypt, if not living with extended family members, the majority of children without parental care are placed in care homes. Research shows that children without parental care, particularly those raised in care homes, generally receive low-quality care. This can lead to adverse effects on their mental health, physical health, developmental growth, sense of belonging, intimacy, social and behavioral competence, and academic performance. Studies also relate institutionalization to problems in attachment and caregiver-infant relationships. The Secure Base Model is a therapeutic caregiving framework that target children who were abused and neglected or experienced loss and separation. The model has five main dimensions that are important for the promotion of security and resilience: availability; sensitivity; acceptance; cooperation; and family membership. This research examines the quality of care and the issue of attachment in children without parental care in Egypt through the perspective of The Secure Base Model. The proposed research questions are: 1) Are caregivers in Egypt aware of their psychological role in caring for children at care homes? 2) To which extent do they apply – or not apply – dimensions of the secure base model? and 3) How are attachment theory and secure base model assumptions applied in the Egyptian context? In-depth interviews were conducted with a sample of 14 caregivers working in care homes and a matched sample of 12 biological mothers for purposes of cultural comparison. The majority of both the caregivers and biological mothers exhibited many of the themes that indicate strengths in their relationship with children. Likewise, the majority of both groups did not exhibit most of the themes that indicate weaknesses in the relationship. The section that showed the highest strengths for both groups was availability. In contrast, the sections on describing the child, acceptance, and cooperation seemed to be weaker. When comparing the results of both groups, the mothers seemed to generally do better than the caregivers. In addition, caregivers showed contradicting feelings of happiness, responsibility, and denial towards the children’s attachment to them, which was not seen in the sample of mothers. Finally, both groups showed difficulty identifying and naming their own and the children’s emotions across all the sections of the interview. The possible reasons of these results within the Egyptian context are discussed, and recommendations are made for improving attachment outcomes for children without parental care at the societal, institutional, and individual levels.